Cytological And Toxicological Properties Of A Medicinal Mushroom - Olorunfemi, D. I.; Akpaja, E. O.; Agbi, B. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2011)
The cytological and toxicological potentials of an extract of a medicinal mushroom, Daldinia concentrica, were evaluated using the Allium cepa model. The extract induced macroscopic and microscopic changes causing a concentration-dependent root growth inhibition and chromosomal aberrations in A. cepa. Compared to the control, treatment with the extract resulted in significant (p<0.05) inhibition of root growth with EC50 value of 1%. The onion root cells showed reduced mitotic indices with corresponding increase in concentration of the mushroom extract. The presence of chromosomal aberrations such as fragments, breaks, bridges and sticky chromosomes in significant (p<0.05) amounts indicates a high rate of genotoxicity in the mushroom extracts. No chromosomal aberration was observed in the control. These observations call for caution in the indiscriminate consumption of Daldinia concentria. Low concentrations and wide spacing of dosage is suggested for the intake of the medicinal mushroom.